RESEARCH ON THE MEDIATING EFFECTS OF RURAL ROADS ON AGRICULTURAL DEVELOPMENT - Liu, Nan; Wen, Jianhua (Economics of Agriculture, 2025)
Rural roads, regarded as the “entrepreneurial capital” of agricultural modernization, serve as critical infrastructure for connecting urban and rural resources and ensuring the smooth circulation of agricultural products. Their level of development profoundly influences rural economic vitality and farmers’ well-being. However, financial constraints in rural areas necessitate the strategic optimization of investment to maximize both the direct benefits and indirect impacts of roads. Based on a composite multiple mediating effect model, this study reveals that rural roads drive agricultural growth through dual pathways of “direct empowerment” and “indirect catalysis.” The results indicate that rural roads directly break the “honeycomb” spatial lock of farmland by promoting land consolidation (e.g., returning farmland to cultivation, merging small plots into larger fields), thereby optimizing spatial layout and establishing a core pathway of “road construction → land transfer → output growth.” Simultaneously, rural roads significantly enhance agricultural mechanization, accelerating the transition toward large-scale and intensive production, while jointly with land optimization, reshaping the rural employment structure.